Atmospheric Pressure Acetylene Detection by UV Photo-Fragmentation and Induced C2 Emission. Issue 1 (January 2013) - Miles, Paul C.; Li, Bo; Li, Zhongshan; Aldén, Marcus
Detection of C2 H2 via UV photo-fragmentation, followed by monitoring the C2 d 3 Πg – a 3 Πu fluorescence, is explored at atmospheric pressure and at temperatures of 295 K, 600 K, and 800 K, for excitation wavelengths 210 to 240 nm using a broadband laser source (~3 cm −1 fwhm). At the lower temperature, C2 emissions correlate closely with C2 H2 Ã←X absorption bands, and the excitation spectra suggest a higher-transition probability for the v″4 = 2 and 3 states than for the v″4 = 0 and 1 states. As temperature increases, the excitation spectra exhibit a higher nonresonant background.